The study and development of the prototype packaging for souvenirs by applying the local wisdom of Mae Hong Son Province. - ไชยนันท์, ไชยเชิด; กิตติพัฒนวิทย์, เจษฎาพล; รินแสงปิน, มนัสพันธ์; ศักดิ์สง่า, นภมินทร์; โอสถาพร, ภควดี (Community and Social Development Journal, 2018)
Abstract The Purposes of this research were, 1) To explore and study about the package of the souvenirs in the Mae Hong Son Province. 2) To design and develop the packages of the souvenirs in the Mae Hong Son Province by adopting uniqueness of the local wisdom in Mae Hong Son Province 3) To evaluate the opinions toward the packages of the souvenirs in Mae Hong Son Province which were designed and developed. The population of this study was divided into two groups which are; 100 customers who use the souvenir products and 17 group of Mae Hong Son souvenir manufactures. The tools used consisted of the Evaluate From before and after the package design and development. After that, Three experts in product design assessed the designed packages by ratting scale. The data was analyzed by using mean and standard deviation and presented in descriptive narration. The research found that 1) The Wisdom of Mae Hong Son has an aptitude thread woven and embroidered a stitching majority Wisdom wasthe invention of the patterned material technical steps of the ancestors of the community. The purpose of the research is to develop all seventeen community enterprise. An assessment was made from the questionnaire survey data from the consumers in Mae Hong Son Province (Pre-designed). It found that the packaging development of souvenir by adopting uniqueness and wisdom of Mae Hong Son province develope the package by adopting the former package which is not attractive customers to purchase. Moreover, some products do not have their own packages, leading to cannot sell the products and the market is not good enough. 2) The customers’ opinions toward the former package of souvenir in Mae Hong Son province show that the level of customers’ satisfaction is low. 3) The opinion toward packaging development of souvenir by adopting uniqueness and wisdom of Mae Hong Son province to develop the new product found that the customers’ opinions toward these, the level of customers’ satisfaction is very good. 4) Opinion of experts were based on the evaluation of new souvenir package in Mae Hong Son province,overview overall. Appropriate utilization were from the products that were more highly usable. 5) Analysis of opinion toward development of souvenir’package in the Mae Hong Son province by adopting uniqueness and local wisdom. It show that safe and clean package is very good. The research proposes a promotion of a “Community Enterprise Group Development Patterns” to constantly packaging knowledge development every year because the package must be developed according to the evolution of the community’s capital and economy.